Meningoencephalitis, Vasculitis, and Abortions Caused by Chlamydia pecorum in a Herd of Cattle. Issue 3 (May 2021) - Struthers, Jason D.; Lim, Ailam; Ferguson, Sylvia; Lee, Jung Keun; Chako, Clemence; Okwumabua, Ogi; Cuneo, Matthew; Valle, Anabell Montiel-Del; Brower, Alexandra
A cow dairy ( n = 2000) in close proximity to a sheep flock had third-trimester abortions and fatalities in cows and calves over a 14-month period. Eighteen of 33 aborted fetuses (55%) had multifocal random suppurative or mononuclear meningoencephalitis with vasculitis. Seventeen of these affected fetuses had intracytoplasmic bacteria in endothelial cells, and 1 fetus with pericarditis had similar bacteria within mesothelial cells or macrophages. Immunohistochemistry for Chlamydia spp. or polymerase chain reaction (PCR) for Chlamydia pecorum or both, performed on brain or pooled tissue, were positive in all 14 tested fetuses that had meningoencephalitis and in 4/4 calves and in 3/4 tested cows that had meningoencephalitis and thrombotic vasculitis. In 1 calf and 11/11 fetuses, C. pecorum PCR amplicon sequences were 100% homologous to published C. pecorum sequences. Enzootic chlamydiosis due to C. pecorum was the identified cause of the late term abortions and the vasculitis and meningoencephalitis in fetuses, calves, and cows. C. pecorum, an uncommon bovine abortogenic agent, is a differential diagnosis in late-term aborted fetuses with meningoencephalitis, vasculitis, and polyserositis.